2013
DOI: 10.6000/1927-520x.2013.02.02.3
|View full text |Cite
|
Sign up to set email alerts
|

Production and Reproductive Performance of Bhadawari Buffaloes in Uttar Pradesh, India

Abstract: Bhadawari is one of the recognized buffalo breeds of India and is famous for high fat content in their milk. Data on production and reproductive traits were collected under Network Project on Bhadawari buffaloes, at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…However [10], observed in Gaolao strain a comparatively less average daily milk yield (3.82 ± 0.092 kg). [1] reported in Bhadawari buffaloes a higher average daily milk yield (6.96 kg).…”
Section: Average Daily Milk Yieldmentioning
confidence: 92%
See 2 more Smart Citations
“…However [10], observed in Gaolao strain a comparatively less average daily milk yield (3.82 ± 0.092 kg). [1] reported in Bhadawari buffaloes a higher average daily milk yield (6.96 kg).…”
Section: Average Daily Milk Yieldmentioning
confidence: 92%
“…However, in Ellichpuri strain a lower milk yield per lactation (1,181.61± 13.90 kg) was found by [5], whereas [21] observed in Nagpuri buffaloes a lower milk yield per lactation (1,023.19 kg). [1] reported that the milk yield per lactation of Bhadawari buffaloes was 1,250.5 kg.…”
Section: Milk Yield Per Lactationmentioning
confidence: 99%
See 1 more Smart Citation